2018
DOI: 10.1177/1533033818790508
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142-3p Promotes Cellular Invasion of Colorectal Cancer Cells by Activation of RAC1

Abstract: Background:Colorectal cancer has been proved more difficult to treat owing to potently malignant metastasis. The present study was aimed to explore the functional role of miR-142-3p in cell migration and invasion of colorectal cancer cells, as well as its underlying mechanism.Materials and Methods:Expressions of miR-142-3p were analyzed in colorectal cancer tissues and cell lines. Ras-related C3 botulinum toxin substrate 1 (RAC1) was predicted as a target of miR-142-3p using software and network resources. SW4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…More than 2,500 miRNAs have been validated in the human genome 10. Recently, miRNAs were found to be dysregulated in most human cancer types, such as lung cancer,11 colorectal cancer,12 breast cancer,13 and bladder cancer 14. Particularly, a variety of miRNAs are aberrantly expressed in cervical cancer 15.…”
Section: Introductionmentioning
confidence: 99%
“…More than 2,500 miRNAs have been validated in the human genome 10. Recently, miRNAs were found to be dysregulated in most human cancer types, such as lung cancer,11 colorectal cancer,12 breast cancer,13 and bladder cancer 14. Particularly, a variety of miRNAs are aberrantly expressed in cervical cancer 15.…”
Section: Introductionmentioning
confidence: 99%
“…According to CRC, three studies have suggested that miR-142-3p is involved in CRC development. On one hand, miR-142-3p promotes cellular invasion by activating RAC1 in colorectal cancer cells [38]. On another hand, miR-142-3p functions as a tumor suppressor by targeting CD133, ABCG2, and Lgr5 in colon cancer cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarce importance in IBD differentiation, the oncogenic role of miR-142-3p is well known, which promotes cellular invasion in colorectal cancer cells by activating RAC1 and the onco-suppressive activity of miR-26a, and inhibits cell aggressiveness by regulating FUT4 in CRC [65,66].…”
Section: Colorectal Diseasesmentioning
confidence: 99%